Data Analysis of Plastic Packaging Production Results at PT. Kailo Sumber Kasih - Manungkalit, Devita M.; Supraptiningsih, Joelianti Dwi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to find out how PT. Kailo Sumber Kasih achieved production results for plastic packaging products according to targets at PT. Kailo Source of Love. [AL1] This research uses descriptive research with a qualitative approach. The object of the research is the production of plastic packaging products at PT. Kailo Source of Love. The data used in this research is secondary data and primary data. Data collection techniques use interview methods, literature study and documentation. The results of this research are that from January 2022 to December 2022, production of plastic packaging products continues to increase, which ultimately results in excess inventory. In the table the average demand is smaller than the amount of production, this is what causes the storage factor to increase. Number of product production at PT. Kailo Sumber Kasih has experienced quite significant increases and decreases, this shows that the productivity of the company's plastic packaging products has experienced increases and decreases, but overall it can be said to be good.